STUDIES ON BIOLOGY OF CATOPSILIA POMONA (FABRICIUS), THE COMMON EMIGRANT AND C. PYRANTHE (LINNAEUS), THE MOTTLED EMIGRANT (LEPIDOPTERA : PIERIDAE) FROM PUNJAB - SEHGAL, JATINDER; ROSE, H.S.; KAURSIDHU, AVTAR (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2010)
The gross morphology and duration of various life history stages has been recorded of two species of genus Catopsilia Hübner viz... pomona (Fabricius) and pyranthe (Linnaeus). The larval and oviposition behaviour of both has been studied in details. Some nectar food plants of adults have also been recorded. Sturnus vulgaris (Linnaeus)(Sturnidae), Hypsitetes madagascariensis (Muller) (Pycnonotidae) and Turdoides caudatus (Dumont) (Timaliidae) have been recorded as bird predators of C. pomona.